2012
DOI: 10.1530/eje-12-0357
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Biological role, clinical significance, and therapeutic possibilities of the recently discovered metabolic hormone fibroblastic growth factor 21

Abstract: Fibroblast growth factor 21 (FGF21), a 181 amino acid circulating protein, is a member of the FGF superfamily, with relevant metabolic actions. It acts through the interaction with specific FGF receptors and a cofactor called β-Klotho, whose expression is predominantly detected in metabolically active organs. FGF21 stimulates glucose uptake in adipocytes via the induction of glucose transporter-1. This action is additive and independent of insulin. β-Cell function and survival are preserved, and glucag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 86 publications
(153 reference statements)
0
61
1
2
Order By: Relevance
“…Serum FGF21 levels were increased significantly in humans with both acute and chronic renal dysfunction during early-to end-stage kidney disease, which might be an adaptive response to diabetes to confer protective effects (30). FGF21 suppresses diabetes-induced inflammation, oxidative stress, and fibrosis in multiple organs, which could be attributed to its effects on maintaining glucose and lipid homeostasis and improving insulin resistance (22,27,56). Similarly, renal protective effects of FGF21 were also observed in our recent study performed in an acute lipotoxic model of type 1 diabetes (56).…”
Section: Discussionmentioning
confidence: 99%
“…Serum FGF21 levels were increased significantly in humans with both acute and chronic renal dysfunction during early-to end-stage kidney disease, which might be an adaptive response to diabetes to confer protective effects (30). FGF21 suppresses diabetes-induced inflammation, oxidative stress, and fibrosis in multiple organs, which could be attributed to its effects on maintaining glucose and lipid homeostasis and improving insulin resistance (22,27,56). Similarly, renal protective effects of FGF21 were also observed in our recent study performed in an acute lipotoxic model of type 1 diabetes (56).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor 21 (FGF21), a liver-derived endocrine factor, has gathered increasing attention because it reduces body fatness and improves glucose tolerance when administrated to rodent models of obesity and type 2 diabetes [54]. FGF21 is potential for inducing the thermogenic program in BAT, and also for driving beige/brite adipocyte recruitment in WAT [55].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Production of this factor takes place in the liver, white adipose tissue, skeletal muscle and pancreas. Glucose and lipid metabolism regulation may depend on FGF21 (Iglesias et al, 2012). Some studies have shown that fasting and feeding may regulate FGF21 expression (Uebanso et al, 2011).…”
Section: Introductionmentioning
confidence: 99%